2015
DOI: 10.1007/s10443-015-9437-4
|View full text |Cite
|
Sign up to set email alerts
|

In-situ Curing Strain Monitoring of a Flat Plate Residual Stress Specimen Using a Chopped Stand Mat Glass/Epoxy Composite as Test Material

Abstract: The curing stresses in a newly proposed bi-axial residual stress testing configuration are studied using a chopped strand mat glass/epoxy specimen. In-situ monitoring of the curing is conducted using dielectric and fibre Bragg grating sensors. It is confirmed that a bi-axial residual stress state can be introduced in the specimens during curing and a quantification of its magnitude is presented. An alternative decomposition method used for converting the dielectric signal into a material state variable is prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…These properties are highly sensitive to the presence of dielectric e.g. metallic nano-particles with high microwave absorption properties [106][107][108][109], and can also be affected by sample preparation [49,56,[110][111][112][113][114][115], moisture [116][117][118], and temperature [119,120]. There has also been a slight confusion of using different terms as 'dielectric constant' in different literatures.…”
Section: Dielectric Properties Of Compositesmentioning
confidence: 99%
“…These properties are highly sensitive to the presence of dielectric e.g. metallic nano-particles with high microwave absorption properties [106][107][108][109], and can also be affected by sample preparation [49,56,[110][111][112][113][114][115], moisture [116][117][118], and temperature [119,120]. There has also been a slight confusion of using different terms as 'dielectric constant' in different literatures.…”
Section: Dielectric Properties Of Compositesmentioning
confidence: 99%
“…Some authors have reported the interesting use of dielectric properties to monitor the progress of reactions in different polymeric systems [23][24][25][26] . The dielectric response of a substance is commonly presented as complex permittivity (*), which can be given by…”
Section: Dielectric Relaxation Spectroscopy (Drs)mentioning
confidence: 99%
“…The formation of the three dimensional polymeric network increased the viscosity of the mixture, and hence the IIM. At 260 minutes, the IIM reached a constant value indicating cure completion [41]. Both the amplitude and velocity of sound associated with the back wall reflection (labelled in Figure 4) are plotted against curing time in Figures 5b and 5c.…”
Section: Bulk Wave Icts Resultsmentioning
confidence: 99%
“…After 260 minutes no change was seen in the degree of conversion data, indicating the end of cure. The evolution of the Imaginary Impedance Maximum (IIM); which corresponds to the maximum value of imaginary impedance recorded in a frequency sweep [41,42], is plotted in Figure 5a. Prior to wetting of the sensor with resin (before 50 minutes, Figure 5a) the magnitude of the IIM was 10 9 -10 10 Ohm, which corresponds to the response of the sensor in air.…”
Section: Bulk Wave Icts Resultsmentioning
confidence: 99%